Stereocontrolled synthesis of halovinylbenziodoxoles by hydro- and iodochlorination of ethynylbenziodoxoles - Wu, Junliang (2020)
We report herein the synthesis of highly substituted and stereochemically well‐defined vinylbenziodoxole (VBX) derivatives through hydrochlorination and iodochlorination of ethynylbenziodoxoles. The hydrochlorination is achieved using pyridine hydrochloride as an HCl source in an anti‐fashion under mild, open‐air conditions to afford a 2‐chlorinated VBX product, which serves as a useful building block for the stereoselective synthesis of trisubstituted alkenes. Meanwhile, iodochlorination with iodine monochloride proceeds in an unusual syn‐pathway, stereoselectively affording a tetrasubstituted VBX derivative.